2009
DOI: 10.1021/ja903817z
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Biomimetic Mineralization of Dense Hydrogel Templates

Abstract: An electric-current-assisted method was used to mineralize dense hydrogels and create hydroxyapatite/hydrogel composites with unique hierarchical structures. The microstructure of the final material can be controlled by the mineralization technique and the chemistry of the organic matrix. A hydroxyapatite/hydrogel composite was obtained with a large inorganic content (approximately 60% of the weight of the organics). After being heated to 1050 degrees C, the sintered inorganic phase has a very uniformly distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 23 publications
2
49
0
1
Order By: Relevance
“…6B2, C2). These results are in accordance with those shown by Liu et al [40] who identified large mineral plates within a water-entrapped polymer hydrogel matrix corresponding to the basal region of the filled water channels and agglomerates of apatite nanocrystals within the gap region of the water channel. However, it is also possible that the crystallised SBFS-aged bonded-dentine interface created using resin A and B may have had similar mechanical characteristics as well as those created by GIC applied on PAA-etched dentine when submitted to tensile tests.…”
Section: Discussionsupporting
confidence: 93%
“…6B2, C2). These results are in accordance with those shown by Liu et al [40] who identified large mineral plates within a water-entrapped polymer hydrogel matrix corresponding to the basal region of the filled water channels and agglomerates of apatite nanocrystals within the gap region of the water channel. However, it is also possible that the crystallised SBFS-aged bonded-dentine interface created using resin A and B may have had similar mechanical characteristics as well as those created by GIC applied on PAA-etched dentine when submitted to tensile tests.…”
Section: Discussionsupporting
confidence: 93%
“…This is a particular problem when working with nanoporous, elastic hydrogels with limited water incorporation. The use of electrical assisted diffusion seems to be a path to promote ion diffusion and true 3D mineralization (Figure 5) [58, 59]. It has been observed that phase separation during the process can result in the formation of microscopic liquid vesicles in the organic matrix that will play a similar role to the vesicles secreted by osteoblasts during bone formation [59].…”
Section: Nanocomposite Approaches For Scaffoldsmentioning
confidence: 99%
“…Here, the vesicles secrete apatitic crystals that subsequently calcify periodically arranged, calcium-binding hole zones with specific amino acid composition in collagen fibers of the extracellular matrix. 79,80 Liu et al 81 created liquid vesicles that entered the hydrogel matrix using a current-mediated ion diffusion method that resulted in mineralization at the interior of a pHEMA hydrogel. The dense hydrogel acted as binding site for the Ca ions and promoted mineralization of nanoapatite.…”
Section: Vesicles Loaded With Ca 2þ and Po 4 3àmentioning
confidence: 99%